Assembly California Legislature For Immediate Release - Bruce F. Allen:::::: (1960)
This two page document is a a letter from Bruce F. Allen sent to all California's mental hospitals to explain that the mental hospital budget for the Department of Mental Hygiene for 1961-62 will be $2,283,000 due to a new Neuropsychiatric Clinic at UCLA. It is also stated that no provision of new drugs, equipment, new types of treatment, or increase numbers of patients will be covered. This is because for the first time in many years, the California Legislature will not be requested by the governor to improve its mental hospitals. This is due to a new policy which allocates a lump sum budget to each agency. This policy will hold Governor Brown's charges he made as Attorney general in which many patient bodies are to be found.